Left-behind regions in Poland, Germany, Czechia: Classification and electoral implications - Josef Bernard; Martin Refisch; Anna Grzelak; Jerzy Bański; Larissa Deppisch; Michał Konopski; Tomáš Kostelecký; Mariusz Kowalski; Andreas Klärner (Johann Heinrich von Thünen-Institut, 2025)
Recently, the notion of left-behind places and regions has gained ground in academic debates on regional inequality and changing electoral landscapes. This paper proposes an approach to conceptualising and measuring regional "left-behindness" in three Central Eastern European countries that goes beyond a dichotomous division of regions into "left-behind" versus "not left-behind". It understands left-behindness as a multi-dimensional continuum, representing regional disparities in living standards and socio-economic opportunities. Our understanding of left-behind plades is based to a large extent on the current economic conditions of the regions and their dynamics, but goes beyond them to include a wider range of socially relevant aspects of the living conditions, including educational attainment, poverty, and the attractiveness of places to live. The paper proposes an approach to measuring regional left-behindness and explores how it explains voting patterns. Thus, the paper is motivated by the seminal arguments of the 'geography of discontent' debate. Its proponents have argued that rising support for populist, right-wing nationalist-conservative and antisystem parties is often closely linked to spatial patterns of regional inequality. This argument has been repeatedly tested in Western European countries, but has remained under-researched in Central Eastern Europe. Using our approach, we were able to confirm the validity of the "geography of discontent" as a central thesis for all three countries studied. The novelty and added value of this study is that it extends the understanding of left-behindness and voting. Our multidimensional approach to left-behindness allows for a comprehensive interpretation of spatial patterns of populist voting in Central Eastern Europe. The relationship between regional left-behindness and voting behaviour varies in strength across different countries. In Czechia, there are strong associations for the parties ANO and SPD, but not for the KSéCM. In eastern Germany, the association between leftbehindness and support for the AfD is weaker, as is the case in Poland for the PiS. Another contribution of the multidimensional concept of left-behindness is the finding that different dimensions of left-behindness have different electoral effects. There appears to be a systematic influence of economic prosperity and relative expansion, which primarily capturesthe contrast between metropolitan areas and their hinterlands on the one hand, versus the rest of the country on the other-not only in terms of economic prosperity and relative expansion, but also in terms of a significant social status hierarchy. Poverty, however, shows a less stable relationship. – – Der Begriff der "abgehängten" Orte und Regionen hat in akademischen Debatten über regionale Disparitäten und sich verändernde Wahllandschaften an Bedeutung gewonnen. Dieses Paper schlägt einen Ansatz zur Konzeptualisierung und Messung regionaler Disparitäten in drei mittel- und osteuropäischen Ländern vor, der über eine dichotomische Unterteilung der Regionen in "abgehängt" versus "nicht abgehängt" hinausgeht. "Abgehängtheit" wird als ein mehrdimensionales Kontinuum verstanden, das regionale Disparitäten in Bezug auf Lebensstandards und sozioökonomische Chancen darstellt. Unser Verständnis von "abgehängten" Regionen basiert weitgehend auf den aktuellen wirtschaftlichen Bedingungen der Regionen und deren Dynamik, geht jedoch darüber hinaus und schließt ein breites Spektrum sozial relevanter Aspekte der Lebensbedingungen ein, einschließlich Bildungsniveau und Armut. Das Paper schlägt einen neuen Ansatz zur Messung regionaler Disparitäten vor und untersucht, wie diese Wahlverhalten erklären. Das Paper nimmt Bezug auf die grundlegenden Argumente der Debatte über die "Geographie der Unzufriedenheit". Darin wird argumentiert, dass die zunehmende Unterstützung für populistische, rechtspopulistische national-konservative und Anti-System-Parteien oft eng mit räumlichen Mustern regionaler Disparitäten verbunden ist. Diese These wurde wiederholt in westeuropäischen Ländern getestet, jedoch in Mittel- und Osteuropa noch unzureichend untersucht. Mit unseren Analysen können wir die Gültigkeit der Annahmen der "Geographie der Unzufriedenheit"für alle drei untersuchten Länder im Grundsatz bestätigen. Die Neuheit und der Mehrwert dieses Papers bestehen darin, dass darin das Verständnis von regionalen Disparitäten und Wahlverhalten erweitert wird. Unser multidimensionaler Ansatz zur Messung regionaler Disparitäten ermöglicht eine umfassende Interpretation räumlicher Muster populistischen Wahlverhaltens in Mittel- und Osteuropa. Die Beziehung zwischen regionalem "Abgehängtsein" und Wahlverhalten variiert in ihrer Stärke zwischen den verschiedenen Ländern. In Tschechien bestehen starke Assoziationen zu den Parteien ANO und SPD, jedoch nicht zur KSéCM. In Ostdeutschland ist der Zusammenhang zwischen "Abgehängtsein" und Unterstützung für die AfD schwächer, ebenso wie in Polen für die PiS. Ein weiterer Beitrag des multidimensionalen Konzepts des "Abgehängtseins" ist die Erkenntnis, dass verschiedene Dimensionen unterschiedliche Wahleffekte haben. Es scheint einen systematischen Einfluss von wirtschaftlichem Wohlstand und regionalem Wachstum zu geben, der sich vor allem in Unterschieden zwischen städtischen Gebieten und deren ländlichem Umland einerseits und dem Rest des Landes andererseits zeigt. Der Zusammenhang zwischen Armut und sozialer Exklusion auf der einen Seite und dem Wahlverhalten auf der anderen Seite ist jedoch weniger stabil.
urn:nbn:de:gbv:253-2025-000006-9
Keywords: D72; O18; O57; 630; Geographie der Unzufriedenheit; politische Geographie; abgehängte Regionen; regionale Disparitäten; Wahlgeographie; Deutschland; Tschechien; Polen; Europäische Union; geography of discontent; political geography; left-behind places; regional disparities; electoral geography; Germany; Czechia; Poland; European Union